Determinants of adopting the internet banking in Bangladesh: Extending UTAUT2 with perceived susceptibility to COVID-19: Extending UTAUT2: Internet Banking Amid COVID-19 (IIUC Business Review, 2026)
This study aims at examining the factors that influence internet banking adoption by Bangladeshi bank customers.  The conceptual model used in this study is based on the extended Unified Theory of Acceptance and Use of Technology (UTAUT2), which is extended by adding perceived susceptibility to COVID-19 to understand the impact of the pandemic on internet banking adoption. Data were collected from a convenience sample of 293 Bangladeshi banking customers through field survey questionnaires. The collected data were analyzed by conducting structural equation modeling (SEM).  The results of the study show that internet banking adoption by banking customers in Bangladesh is significantly influenced by behavioral intention, which notably depends on price value, social influence and hedonic motivation; however, behavioral intention is independent of effort and performance expectancy. Moreover, the result revealed a significant direct impact of facilitating conditions and habit on internet banking adoption, but no significant relationship was found between perceived susceptibility to COVID-19 and internet banking adoption. The study offers worthy findings to the banks as well as policymakers to make decisions regarding internet banking promotion, financial inclusion and digitalization of the financial sector.IIUC Business Review, Vol.-12, Issue-1, December 2023, pp. 119-142